Water conservation in Cape Town : developing a municipal strategy for sustainable resource management - Powell, Mark Garikayi; Koelble, Thomas (London : SAGE Publications: SAGE Business Cases Originals, 2018)
This case finds municipal leaders in Cape Town, South Africa, in a state of crisis as they face the effects of a 1-in-300-year drought plaguing the region. It is early 2017 – the peak of the dry season in Cape Town – and Mario Carelse, the senior manager of water demand management at the City's Department of Water and Sanitation, is briefing his departmental executives on the state of water consumption and availability in order to develop a strategy for managing the limited water stocks. South Africa's Constitution ensures the right to water access for all citizens and a base quantity of free water is allocated for all. Yet the department is falling short of its goal to keep non-revenue water (NRW) usage below 20%, a threat to both environmental and economic sustainability. Ultimately, Carelse and his colleagues want to change consumer behaviour, but they are not yet sure how. The case follows their discussion as they process the key considerations for reducing water usage: the state of infrastructure and available resources, economic inequality across the population, the constitutional right to water access, and the relationship between the city and its citizens.
Originally Published InPowell, M. G., & Koelble, T. (2018). Water conservation in Cape Town: Developing a municipal strategy for sustainable resource management. 2018-3. Cape Town, South Africa: Graduate School of Business, University of Cape Town.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Water demand management -- South Africa -- Cape Town -- Case studies; Water resources development -- South Africa -- Cape Town -- Case studies